PERFIL COGNITIVO EM IDOSAS DE DOIS SERVIÇOS PÚBLICOS DE REFERÊNCIA EM SÃO LUÍS-MA - Correia, Marcius Vinicius Goncalves (2007)
As the population grows old, there is a proportional increase of cognitive disturbances. Due to the great relevance, this study aims to establish a descriptive study about the cognition level and correlated socio-demographic variables, in women ranging from sixty to eighty years old, in two public health services in the city of São Luís-MA. For a period of four months, a closed questionnaire which contained the socio-demographic variables and the Mental Condition Mini Examination (MEEM), was applied. A number of eighty voluntaries were evaluated in the Neurology clinics of the University Hospital President Dutra and State Hospital Carlos Macieira. The results were: 31,2% were classified by MEEM with cognitive disturbances; 71,4% in the 81-85 age bracket. In the population distribution according to schooling time, 54,9% of those having seven years of school were classified as having cognitive disturbances. As for the referred ethnicity and cognition level, 44.8% of mullatos presented cognitive disturbances. As for income and cognition level, it was observed that 30,4% of the volunteers who presented an income level lower than one to two minimum wage, were classified with cognitive disturbances. From the thirty-three volunteers that had direct care, 57,6% (19) presented cognitive disturbances. As for the referred morbidities, it was observed that 58,75% were referred to as having Systemic Arterial Hypertension; regarding life styles, 12,5% were referred to as smokers. The study becomes relevant because it provides epidemiologic substract for more complex methodological studies in order to promote improvement in the elderly mental public health in the area.